Modelling Combined Intravenous Thrombolysis and Mechanical Thrombectomy in Acute Ischaemic Stroke: Understanding the Relationship between Stent Retriever Configuration and Clot Lysis Mechanisms - Emily Louise Manchester (MDPI AG, 2021)
Background: Combined intravenous thrombolysis and mechanical thrombectomy (IVT-MT) is a common treatment in acute ischaemic stroke, however the interaction between IVT and MT from a physiological standpoint is poorly understood. In this pilot study, we conduct numerical simulations of combined IVT-MT with various idealised stent retriever configurations to evaluate performance in terms of complete recanalisation times and lysis patterns. Methods: A 3D patient-specific geometry of a terminal internal carotid artery with anterior and middle cerebral arteries is reconstructed, and a thrombus is artificially implanted in the MCA branch. Various idealised stent retriever configurations are implemented by varying stent diameter and stent placement, and a configuration without a stent retriever provides a baseline for comparison. A previously validated multi-level model of thrombolysis is used, which incorporates blood flow, drug transport, and fibrinolytic reactions within a fibrin thrombus. Results: Fastest total recanalisation was achieved in the thrombus without a stent retriever, with lysis times increasing with stent retriever diameter. Two mechanisms of clot lysis were established: axial and radial permeation. Axial permeation from the clot front was the primary mechanism of lysis in all configurations, as it facilitated increased protein binding with fibrin fibres. Introducing a stent retriever channel allowed for radial permeation, which occurred at the fluid-thrombus interface, although lysis was much slower in the radial direction because of weaker secondary velocities. Conclusions: Numerical models can be used to better understand the complex physiological relationship between IVT and MT. Two different mechanisms of lysis were established, providing a basis towards improving the efficacy of combined treatments.